2014
DOI: 10.1097/jom.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being, Health, and Productivity Improvement After an Employee Well-Being Intervention in Large Retail Distribution Centers

Abstract: There is evidence that programs designed to improve well-being within a workforce can be used to significantly and positively impact employee health and productivity, which should result in reduced health care costs, improved employee productivity, and increased overall profitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Hence, this study has not yet been able to investigate concrete mechanisms. Possible mechanisms between HL and work productivity are: 1) In health literacy studies, some researchers have suggested that an association between health literacy and health behavior (20) , (21) ; 2) On the other hand, health behaviors may have influenced work performance (i.e., positive health behaviors lead to preventive health measures and investments in health, which can improve and maintain the health status of workers and increase work performance) (3) . Therefore, HL appears to lead to positive health behavior, which results in good work performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this study has not yet been able to investigate concrete mechanisms. Possible mechanisms between HL and work productivity are: 1) In health literacy studies, some researchers have suggested that an association between health literacy and health behavior (20) , (21) ; 2) On the other hand, health behaviors may have influenced work performance (i.e., positive health behaviors lead to preventive health measures and investments in health, which can improve and maintain the health status of workers and increase work performance) (3) . Therefore, HL appears to lead to positive health behavior, which results in good work performance.…”
Section: Discussionmentioning
confidence: 99%
“…Health behaviors influence work performance (3) ; positive health behaviors lead to preventive health measures and investments in health, which can improve and maintain workers’ health status and increase work performance (4) , (5) . Recent studies show that health literacy (HL), defined as “the cognitive and social skills which determine the motivation and ability of individuals to gain access to, understand and use information in ways which promote and maintain good health,” (6) is necessary to improve health behaviors (7) .…”
Section: Introductionmentioning
confidence: 99%
“…The results from the present study provide insights that may assist researchers, health promoting organisations, practitioners, insurance companies, occupational physicians, various government departments, and labour unions to more effectively generate interest and action from employers to create improvements in employee health outcomes and associated work-focussed benefits. While the findings are most applicable to the Australian context, they may have relevance for international settings given the universal applicability of workplace health promotion and the growing trend towards the implementation of health and wellbeing programs in the workplace [ 13 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence surrounding the value of workplace health promotion in positively influencing employees’ health and wellbeing via changes to their health behaviours is growing [ 13 19 ]. Several factors influencing the implementation of workplace health promotion programs have been identified [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has highlighted numerous benefits associated with worksite wellness programs (Abell & Main, ; Beck, Hirth, Jenkins, Hirth, Jenkins, Sleemand, & Zhang, ; Carter, Kelly, Alexander, & Holmes, ). Wellness programs traditionally focus on achieving outcomes such as reductions in medical costs, lowered employee health risks, decreased absenteeism and improved morale, with increased productivity also being examined (HERO, ; Rajaratnam, Sears, Shi, Coverley, & Pope, ). Not only have health improvements been documented as a result of these programs, but positive economic‐related outcomes have also been identified (Gubler, Larkin, & Pierce, ; Kaspin, Gorman, & Miller, ; Schwartz et al, ).…”
Section: Introductionmentioning
confidence: 99%